Konsep Manajemen Kurikulum - Elizasri, Elizasri; Jamilus, Jamilus (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The curriculum is one of the most decisive components in an education system, because of that the curriculum is atool to achieve educational goals and at the same time as a guide in the implementation of teaching at all types and levels of education. The educational goals of a nation or country are determined by the philosophy and outlook on life of that nation or country. Differences in philosophy and outlook on life of a nation or country lead to different goals to be achieved in education and at the same time will affect the country. The Islamic Education Curriculum has a very important position in shaping one's personality. Fact. By understanding the curriculum, educators can select and determine appropriate and appropriate learning objectives, methods, techniques, teaching media and teaching evaluation tools. For this reason, in conducting studies the success of the education system is determined by realistic goals, acceptable to all parties, good facilities and organization, high realistic work intensity and an effective curriculum. Therefore, it is only natural for educators and educational staff in the field of Islamic education to understand the curriculum and try to develop it.